The Impact of Polymer on the Productivity and Photosynthesis of Soybean under Different Water Levels - Lucas Felisberto Pereira; Walter Quadros Ribeiro Júnior; Maria Lucrecia Gerosa Ramos; Guilherme Filgueiras Soares; Cristiane Andréa de Lima Guimarães; Sebastião Pedro da Silva Neto; Onno Muller; Christina Cleo Vinson; André Ferreira Pereira; Thomas Christopher Rhys Williams (Agronomy, 2022)
In order to practice sustainable and resource-efficient agriculture, the use of new technologies such as water-retaining polymers is essential. The objective of this study was to evaluate the effect of a polymer incorporated into the soil on gas exchange and yield under different water regimes (WR) in three soybean cultivars. The experiment was conducted at Embrapa Cerrados under field conditions in 2016 and 2017, using three different cultivars (BRS 5980IPRO, NA 5909RG and BRS 7280RR). Soybean cultivars were submitted to four water regimes (representing 30%, 50%, 83% and 100% of evapotranspiration replacement, namely WR1, WR2, WR3 and WR4). No beneficial results were observed in 2016 with Polymer. Most of the reductions in photosynthesis and transpiration by adding the polymer can be attributed to stomatal control, but such reductions did not influence productivity. In 2017, the yield was higher using Polymer in WR4 and WR3 by 40 to 20%, depending on the cultivar. Under severe stress (WR2 and WR1), reduced gas exchange was obtained with Polymer, but the yield was not reduced. These results indicate that Polymer contributed to the prolongation of photosynthetic activity during the reproductive phase of soybean and may represent a potential strategy for increasing yield under moderate drought stress.